Implementation of Actio Pauliana in the Construction Services Contract for the Construction of the National Strategic Project Sgar Mempawah - Cindy; Yuwono Prianto (Journal of Law, Politic and Humanities, 2024)
The purpose of this study is to determine the implementation of actio pauliana by the parties in the event of default on the contract and what legal protection can be given to the contractor when actio pauliana executed /performed. This study is a normative-Empirical Legal Research, which combines aspects of normative jurisprudence with empirical jurisprudence. Normative aspects include the study of legislation and legal literature related to actio pauliana and construction services law. The results of the study show that the application of actio pauliana must also take into account the legal protection of third parties, especially contractors in good faith. The law recognizes that a buyer in good faith remains entitled to legal protection in order to obtain his rights to the goods he legally purchased. If the buyer is unable to obtain the goods he has purchased as a result of the cancellation of the legal act through actio pauliana, they are entitled to claim damages. It is also important to note that not all legal acts can be annulled through the actio pauliana. Legal acts committed in the interests of the company, not in personal interests, may be excluded from cancellation. This suggests that the law also takes into account the context and purpose of the legal act committed.